Enhancing Delegate Satisfaction through Green Practices at Bali Nusa Dua Convention Center - Muda, Yoga Angga; Armoni, Ni Luh Eka; Bagiastuti, Ni Ketut; Septevany, Elvira (Politeknik Negeri Bali, 2025)
The purpose of this study was to determine the effect of green practices on delegate satisfaction at the Bali Nusa Dua Convention Center (BNDCC). The data collection method used was distributing questionnaires to delegates who had held meetings at the Bali Nusa Dua Convention Center from January 2024 to May 2024 and the observation. In this study, the author used the Slovin Formula, 98 samples from 6200 populations. The results show that green practice significantly affects delegate satisfaction at the Bali Nusa Dua Convention Center. The results of the determination coefficient (R-squared) test are 0.567 (56.7%). The implementation of green practices results in an impact on guest satisfaction. The correlation between green practice implementation and delegate satisfaction is approximately 56.7%. This indicates that BNDCC's green practices positively influence delegation of satisfaction, interest in revisiting, and willingness to recommend. The most influential indicator on guest satisfaction is BNDCC, which has been green certified and has also implemented energy saving by installing LED lights for lighting. Delegates' satisfaction can also be seen in wanting to hold events at BNDCC with sustainability themes. The questionnaire results given to the delegates who held this event also recommended carrying out activities here, especially with the theme of sustainability.